Induction of Cross-Reactive and Protective Antibody Responses After DNA Vaccination With MHCII-Targeted Stem Domain From Influenza Hemagglutinin - Grødeland, Gunnveig; Baranowska-Hustad, Marta; Abadejos, Justin; Blane, Tanya R.; Teijaro, John; Nemazee, David; Bogen, Bjarne (Frontiers in Immunology, 2020)
Novel and more broadly protective vaccines against influenza are needed to efficiently meet antigenic drift and shift. Relevant to this end, the stem domain of hemagglutinin (HA) is highly conserved, and antibodies specific for epitopes located to the stem have been demonstrated to be able to confer broad protection against various influenza subtypes. However, a remaining challenge is to induce antibodies against the poorly immunogenic stem by vaccination strategies that can be scaled up for prophylactic vaccination of the general population. Here, we have developed DNA vaccines where the conserved stem domain of HA from influenza A/PR/8/34 (H1N1) and A/Shanghai/2/2013 (H7N9) were targeted towards MHC class II molecules on antigen presenting cells (APC) for increased immunogenicity. Each of these vaccines induced antibodies that cross-reacted with other subtypes in the corresponding phylogenetic influenza groups. Importantly, when mixing the MHCII-targeted stem domains from H1N1 and H7N9 influenza viruses into one vaccine bolus, we observed broad protection against candidate stains from both phylogenetic groups 1 and 2.